In situ catalyzed Boudouard reaction of coal char for solid oxide-based carbon fuel cells with improved performance - Jiao, Y.; Tian, W.; Chen, H.; Shi, H.; Yang, B.; Li, C.; Shao, Zongping; Zhu, Z.; Li, S. (Elsevier Ltd, 2015)
© 2014 Elsevier Ltd. The use of industrial coal char as a fuel source for an anode-supported solid oxide-based carbon fuel cell (SO-CFC) with a yttrium-stabilized zirconia electrolyte and La0.8Sr0.2MnO3 cathode was investigated. Both the Boudouard reactivity and electrochemical performance of the coal char samples are higher than those of activated carbon samples under the same conditions. The inherent catalytic activity of the metal species (FemOn, CaO, etc.) in the coal char mineral matter leads to good cell performance, even in the absence of an external catalyst. For example, the peak power density of a cell fueled with pure coal char is 100mWcm-2 at 850°C, and that of a cell fueled with coal char impregnated with an FemOn-alkaline metal oxide catalyst is 204mWcm-2. These results suggest that using coal char as the fuel in SO-CFCs might be an attractive way to utilize abundant coal resources cleanly and efficiently, providing an alternative for future power generation.